Fullerene–Graphene Acceptor Drives Ultrafast Carrier Dynamics for Sustainable CdS Photocatalytic Hydrogen Evolution. (14th March 2022) - Wang, Wenchao; Tao, Ying; Fan, Jinchen; Yan, Zhiping; Shang, Huan; Phillips, David Lee; Chen, Ming; Li, Guisheng
Abstract: Ultrafast excited‐state decay and intrinsic charge carrier recombination restrain the photoactivity enhancement for solar‐to‐H2 production. Here, a CdS‐fullerene/graphene (CdS‐F/G) photocatalyst is synthesized for enhancing visible‐light‐driven hydrogen generation from earth‐abundant water. The CdS‐F/G shows ultrafast interfacial electrons/holes transfer and holes self‐trapping process in photocatalysis. The in‐situ dynamic study from transient absorption spectroscopy reveals the sub‐microsecond‐lived excited states (≈172.6 ns), interfacial electron transfer (≈30.3 ps), and hole trapping (≈44.0 ps) in the CdS‐F/G photocatalyst. The efficient active species transportation and prolonged lifetime significantly enhance the charge separation state survival, increasing the photoactivity and photostability. Consequently, visible‐light activity enhancement (>400%) of H2 evolution reaction (HER) is obtained at the CdS‐F/G photocatalyst with high stability (>36 h). The 127.2 µmol h −1 g −1 performance corresponding to a quantum efficiency of 7.24% at 420 nm is not only higher than the case of pristine CdS (29.2 µmol h −1 g −1 ) but also much higher than that of CdS‐Pt photocatalyst (73.8 µmol h −1 g −1 ). The cost‐effective CdS‐F/G photocatalyst exhibits a great potential for sustainable and high‐efficiency photocatalytic water splitting into clean energy carriers. Moreover, the optimized electronic structure associated with interfacial electrons/holes transfer and holes self‐trapping promotes overall water splitting for H2 and O2 generation. Abstract : Fullerene–graphene (F/G) boosts the excited state survival to sub‐microsecond and overall improves the photocatalytic activity/stability of CdS. The lower Fermi level of F/G enables it to collect charge carriers from the CdS photocatalyst for highly efficient interfacial electrons/holes transport and H2 production. As a result, the enhanced H2 production rate demonstrates a great potential to replace noble metal (Pt) for solar‐to‐H2 conversion.